Earth sciences and history in the work of Correia da Serra (1751-1823) - Simões, Ana (2017)
We thank Junia Furtado for the invitation to participate in this issue and the anonymous referees for comments and suggestions. The research for this article was supported by the Project UID/HIS/00286/2013 of the Portuguese Foundation for Science and Technology (FCT) which sponsors the research group Centro Interuniversitário de História das Ciências e Tecnologia (CIUHCT), to which we all belong.